The Effect of Organizational Inclusive Cues and Inclusive Cues Incongruence on Application Intentions Mediated by Perceived Organizational Hypocrisy among Generation Z Students of the Faculty of Business and Economics (FBE), Universitas Islam Indonesia (U - Aurellia Belva Putri Purnomo (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
In the digital era, Generation Z tends to use job search platforms to research companies before applying. During this information gathering process, discrepancies are often found between statements of inclusivity and online reviews of employee experiences on these job search platforms. This study aims to analyze how organizational inclusive cues and incongruence of inclusive cues influence the application intentions of Generation Z alumni and students at the Faculty of Economics and Business (FBE) UII, mediated by perceptions of organizational hypocrisy. This study used a purposive sampling method with 250 respondents consisting of Generation Z alumni and final-year students at the Faculty of Economics and Business (FBE) UII who are currently or have used job search platforms. Data collection was conducted by distributing questionnaires. The results of this study indicate that organizational inclusive cues have a significant positive effect on application intentions, while incongruence of inclusive cues has a significant negative effect on application intentions. This study found that strongly communicated inclusive cues can increase skepticism and perceptions of organizational hypocrisy, which in turn reduces application intentions. Conversely, incongruence of inclusive cues was found to weaken application intentions by increasing perceptions of organizational hypocrisy. Thus, this study confirms that consistency in inclusive communication and implementation plays a crucial role in preventing 'inclusivity washing'.